1984
DOI: 10.1007/bf02904400
|View full text |Cite
|
Sign up to set email alerts
|

Malt carboxypeptidase catalyzed aminolysis reactions

Abstract: Malt carboxypeptidase catalyzes the formation of peptide bonds using N-benzoyl-arginine esters as acyl components and amino acid amides or amino acid methyl esters as nucleophiles. With seven different nucleophiles yields of 50-95% were obtained while no aminolysis was observed with H-Pro-NH2 and H-GIu-a-NH2. The enzyme is easily saturated with nucleophile indicating the formation of a complex between nucleophile and acyl-enzyme intermediate prior to deacylation. The nature of the side-chain of the amino acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1984
1984
1988
1988

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…The structures of the acyl and amine components which may participate in the reaction are determined by the specificity of the enzyme used, and studies in this laboratory have revealed that serine carboxypeptidases, e.g. carboxypeptidase Y and the malt carboxypeptidases, as expected, catalyze only aminolysis reactions with amino acids and amino acid derivatives as amine components (33,38,196,197) as opposed to endopeptidases that in addition to amino acid derivatives also accept polypeptides as nucleophiles (136,149). Consequently, when a carboxypeptidase is used a peptide chain will only be elongated by a single amino acid residue in each aminolysis reaction.…”
Section: Use Of Serine Carboxypeptidases In Peptide Synthesismentioning
confidence: 98%
See 3 more Smart Citations
“…The structures of the acyl and amine components which may participate in the reaction are determined by the specificity of the enzyme used, and studies in this laboratory have revealed that serine carboxypeptidases, e.g. carboxypeptidase Y and the malt carboxypeptidases, as expected, catalyze only aminolysis reactions with amino acids and amino acid derivatives as amine components (33,38,196,197) as opposed to endopeptidases that in addition to amino acid derivatives also accept polypeptides as nucleophiles (136,149). Consequently, when a carboxypeptidase is used a peptide chain will only be elongated by a single amino acid residue in each aminolysis reaction.…”
Section: Use Of Serine Carboxypeptidases In Peptide Synthesismentioning
confidence: 98%
“…However, the limited data must be evaluated with caution since the situation where k2,~ k3 cannot be distinguished from k2 k3 as long as only the steady-state kinetics of hydrolysis reactions have been studied. Determination of kinetic parameters in the presence of added nucleophiles is more informative and such studies have been performed with malt carboxypeptidase I in this laboratory using ZLys 89 as substrate and H-Val-NH2 as added nucleophile (33). Under these conditions the acyl-enzyme intermediate is partitioned between hydrolysis and aminolysis products, i.e.…”
Section: E + S E Es -) Es' > E + P2mentioning
confidence: 99%
See 2 more Smart Citations
“…The serine carboxypeptidases play an important role in this process and MmOLA ( 17,18,19) has presented evidence for the presence in malt of five such enzymes with complementary specificites. In this laboratory two of these have been isolated by affinity chromatography and their enzymatic properties and sequences have been determined (2,3,4,6,7,23,24). The isolation and characterization of CPD-Mm is reported here.…”
Section: Introductionmentioning
confidence: 99%